Correlation between environmental DEET exposure and the mortality rate of cancer survivors: a large-sample cross-sectional investigation - Lingjuan Liu; Weicheng Qin; Lixin Nie; Ximing Wang; Xiulan Dong (BMC Cancer)
Abstract Background N, N-Diethyl-meta-toluamide (DEET) is the predominant active ingredient found in insect repellents utilized by consumers. Exposure to DEET has been associated with notable risks to human health. Nonetheless, there is a scarcity of extensive cohort studies investigating the precise correlation between DEET exposure and mortality rates among cancer survivors. The objective of this study is to thoroughly evaluate the connection between DEET exposure and mortality rates in cancer survivors. Methods This study employed individual samples obtained from the National Health and Nutrition Examination Survey (NHANES). Utilizing data from NHANES spanning 2007 to 2016, this study incorporated a cohort of 5,859 cancer survivors for subsequent analysis, following the exclusion of incomplete datasets. Through subgroup analysis, the research examined the impact of quartile levels of 3-diethyl-carbamoyl benzoic acid (DCBA), the primary metabolite of DEET, on cancer survivors across various subgroups within the broader population. Furthermore, the research utilized a multivariable Cox proportional hazards regression model and Kaplan-Meier (KM) curves to investigate the relationship between 3-diethyl-carbamoyl benzoic acid (DCBA), a principal metabolite of DEET, and mortality rates in individuals who have survived cancer. Results The study identified an association between specific quartiles of DCBA concentration and a decreased risk of all-cause mortality among cancer survivors, specifically in the second (Q2: 0.665–1.95) and third quartiles (Q3: 1.95–6.845). Furthermore, a significant correlation was observed between the third quartile and cancer-specific mortality (Q3: 1.95–6.845), as well as between the second quartile and non-cancer mortality (Q2: 0.665–1.95). The quartiles of DCBA concentration exhibit a statistically significant correlation with total deaths (P < 0.001), cancer-specific deaths (P = 0.009), and non-cancer deaths (P < 0.001) among cancer survivors. The correlation between DCBA and reduced mortality risk in cancer survivors is particularly notable among females and individuals of non-Hispanic Black descent. Conclusion The detection of DCBA in the urine of adult cancer survivors is strongly associated with increased mortality risks, particularly among females and non-Hispanic Black individuals, warranting further investigation and targeted interventions.